Aesthetic Activism and the Carnivalesque in the Urban Social Movements - Tunali, Tijen (Street Art & Urban Creativity, 2023)
This paper considers the ways in which changes and experimentations in the realm of aesthetics ,as well as in the new forms of political participation and representation in an era of global revolt, have resulted in a deep connection between the aesthetics and politics of civil disobedience, political activism and artistic representation. Specifically, the discussion is based on a comparative analysis of the urban activism of the Carnival Against Capital protests in London and Seattle, the Occupy Movement in New York, and the Gezi Park Movement in Turkey where the aesthetics of active participation represents a new kind of politicization—collective memory and language, sensual festivity and the forming of communitas—that goes beyond the conventional understanding of the convergence of politics and art. The author focuses on the notable carnivalesque character in those protests—the costumes, the masks, the performances, the interventional tactics and the aesthetics of community building. Based on the theories of aesthetics and rebellion the paper proposes the concept of carnival aesthetics as the study of the sensuous and subversive experience of the multitude when marching, throwing slogans, battling with police forces behind the barricades, performing and dancing together on the streets. Here carnivalesque aesthetics are employed as a means to create diversity, creativity, decentralization, horizontality, egalitarianism and direct action—the political principles that are at the heart of the recent protests. The discussion demonstrates that while thriving authoritarianism depends on disciplined individuals and the crisis in democracy, carnival aesthetics during protests present radicalized social relations that are increasingly becoming the core of the current social, cultural and environmental struggles around the world.